Improving a medical student feedback with a clinical encounter card. - Ozuah PO; Reznik M; Greenberg L (Ambulatory Pediatrics)
OBJECTIVE: We previously developed a Clinical Encounter Card (CEC) for use in medical student feedback. However, no prior studies have investigated the effectiveness of the CEC. The objective of our study was to determine whether use of the CEC would increase medical students' perception of the feedback they received. METHODS: We conducted a time-series repeated-measures experimental study at a pediatric clerkship site. The study included a crossover design with experimental and control arms. Third-year medical students on the ambulatory rotations were the experimental arm, and inpatient students were the control arm. Students and faculty in the experimental arm received the CEC, which listed 7 feedback domains: history and interviewing, physical examination, oral presentation, written notes, patient assessment, management plan, and professionalism. We used a 10-point Likert-type scale to record responses of students weekly regarding their perceptions of having received feedback in the 7 domains. Multivariate analysis of variance for repeat measures tested mean differences in continuous variables, and Mann-Whitney U rank order sum tested ordinal rank differences. RESULTS: We received 504 reports from students regarding the feedback they received. We found statistically significant improvements in 6 feedback domains for experimental subjects: history/interviewing, physical examination, oral presentation, written notes, patient assessment, and management plan. There was no improvement in feedback received about professionalism. CONCLUSIONS: Use of the CEC resulted in students' perceiving increased feedback as evidenced by significant improvements in several medical student feedback domains.